PROSTATITIS AS AN INITIAL PRESENTATION FOR GRANULOMATOSIS WITH POLYANGIITIS - Butt, Nauman Ismat; Yonus, Raheel; Tareen, Muhammad Qasim Khan; Farman, Sumaira; Ahmad, Nighat Mir; Ahmad, Amna (Journal of Ayub Medical College Abbottabad, 2022)
Granulomatosis with polyangiitis (GPA) is an uncommon pauci-immune small-vessel necrotising granulomatous vasculitis mostly seen in age 45-60 years. We present the case of a formerly healthy 44 years old male presenting with dysuria and intermittent urinary retention for 8 months, not responding to empirical antibiotic therapy and TURP. A prostate biopsy showed necrotising granulomatous prostatitis. Urinalysis demonstrated persistent pyuria and haematuria, but cultures showed no growth. Subsequently he complained of fever, cough, dyspnoea and skin ulcers. CT of the chest showed multiple cavitatory lesions and pleural effusion. On work up, c-ANCA was positive and a diagnosis of granulomatosis with polyangiitis was established. This depicts a rarely seen presentation of prostatitis as the initial feature of GPA.